1989
DOI: 10.1093/jnci/81.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Cervical Cancer and Smoking in Latin America

Abstract: A case-control study of 667 patients with invasive squamous cell carcinoma of the cervix and 1,430 controls from four Latin American countries showed an age-adjusted relative risk (RR) of 1.2 [95% confidence interval (CI) = 1.0-1.4] for women who had ever smoked, with risk rising to 1.7 (95% CI, 0.8-3.6) for women who smoked greater than or equal to 30 cigarettes per day. The associations were practically eliminated after adjustment for the number of sexual partners and alcohol consumption, probably a surrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 22 publications
1
24
1
2
Order By: Relevance
“…2 Cigarette smoking was very rare in our study and unrelated to cervical dysplasia. 25,36,40 In contrast, chewing tobacco use was associated with HSILs and was more frequent among women with ICC. Even though chewing tobacco use was rare, found mostly among women of low educational level, public health authorities must be made aware of the benefits to women's health that would result from preventing addiction to chewing tobacco in Africa.…”
Section: Discussionmentioning
confidence: 94%
“…2 Cigarette smoking was very rare in our study and unrelated to cervical dysplasia. 25,36,40 In contrast, chewing tobacco use was associated with HSILs and was more frequent among women with ICC. Even though chewing tobacco use was rare, found mostly among women of low educational level, public health authorities must be made aware of the benefits to women's health that would result from preventing addiction to chewing tobacco in Africa.…”
Section: Discussionmentioning
confidence: 94%
“…Individuals with a history of smoking have an increased risk for condylomata acuminata [164]. A dose-dependent association between cigarette smoking and the presence of high-risk HPV types as detected by consensus PCR in cervical smears of 181 women remained significant after adjust ment for age at first intercourse and lifetime number of sexual partners [169], That smoking acts synergistically with HPV for cervical carcinogenesis or just increases the risk for HPV infection awaits further clarification: in a case-control study, adjustment for HPV could decrease relative risks between smoking and SILs [ 129], whereas in another study an association was only found in HPV-positive women [170].…”
Section: Smokingmentioning
confidence: 98%
“…Inhalation of air contaminated through the combustion of tobacco (i.e., cigarette smoking) has been amply documented to cause cancer and also cervical neoplasia and invasive cancer. [1][2][3][4][5] Inhalation of air contaminated through the combustion of coal, wood and straw has been related to lung cancer 6,7 and cancers of the head and neck. 8,9 In a casecontrol study of invasive cervical cancer in Honduras, 10 we presented evidence suggestive of an increased risk of invasive cervical cancer among women who had used wood as fuel in the kitchen over many years.…”
mentioning
confidence: 99%